Pemberdayaan Masyarakat Dalam Pengentasan Stunting Di Jorong Sungai Talang - Sari, Wita Purnama; Fadila, Hana; Mulya, Sinta April; Ferza, Zilma; Neri, Refi Febria (Jurnal Dedikasia : Jurnal Pengabdian Masyarakat, 2023)
This community service activity  was motivated by  low the participation of people at  Jorong Sungai Talang to join social program that collage students of KKN PPM Terpadu Tuah Sakato 202 done  there  actively.  People seen like uncare with the collage students that do KKN program there and people just focus on their activities.  Because of that research about correlation between  peoples’ background of work with their participation  in any program at their village was needed. So the aim of this research was to find out the correlation between peoples’ background work with their participation to join the social program at their village. To get the answer of activity question  of this activity used descriptive qualitative. Miles and Huberman model was technic analysis of the data used in this research. People around  Jorong Sungai Talang were informant of this activity. The instrument use in this activity was observation, documentation and interview. This activity got several result. First the people at Jorong Sungai Talang just join the social program in cleanliness only. Then in any other social program they can not participation actively yet because their mindset which said that the day is the time to focus in garden.